Two-Stage Conversion of High Free Fatty Acid Jatropha curcas Oil to Biodiesel Using Brønsted Acidic Ionic Liquid and KOH as Catalysts - Subrata Das; Ashim Jyoti Thakur; Dhanapati Deka (The Scientific World Journal)
Biodiesel was produced from high free fatty acid (FFA) Jatropha curcas oil (JCO) by two-stage process in which esterification was performed by Brønsted acidic ionic liquid 1-(1-butylsulfonic)-3-methylimidazolium chloride ([BSMIM]Cl) followed by KOH catalyzed transesterification. Maximum FFA conversion of 93.9% was achieved and it reduced from 8.15 wt% to 0.49 wt% under the optimum reaction conditions of methanol oil molar ratio 12 : 1 and 10 wt% of ionic liquid catalyst at 70°C in 6 h. The ionic liquid catalyst was reusable up to four times of consecutive runs under the optimum reaction conditions. At the second stage, the esterified JCO was transesterified by using 1.3 wt% KOH and methanol oil molar ratio of 6 : 1 in 20 min at 64°C. The yield of the final biodiesel was found to be 98.6% as analyzed by NMR spectroscopy. Chemical composition of the final biodiesel was also determined by GC-MS analysis.